Pregnancy weight gain in twin gestations and maternal and child health outcomes at 5 years - Bodnar, Lisa M. (Int J Obes (Lond), 2021)
OBJECTIVE: Current guidelines for maternal weight gain in twin pregnancy were established in the absence of evidence on its longer-term consequences for maternal and child health. We evaluated the association between weight gain in twin pregnancies and the risk of excess maternal postpartum weight increase, childhood obesity, and child cognitive ability. METHODS: We used 5-year follow-up data from 1000 twins born to 450 mothers in the Early Childhood Longitudinal Study – Birth Cohort, a nationally representative U.S. cohort of births in 2001. Pregnancy weight gain was standardized into gestational age- and prepregnancy body mass index (BMI)-specific z-scores. Excess postpartum weight increase was defined as ≥10 kg increase from prepregnancy weight. We defined child overweight/obesity as BMI ≥ 85(th) percentile, and low reading and math achievement as scores one standard deviation below the mean. We used survey-weighted multivariable modified Poisson models with a log link to relate gestational weight gain z-score with each outcome. RESULTS: Excess postpartum weight increase occurred in 40% of mothers. Approximately 28% of twins were affected by overweight/obesity, and 16% and 14% had low reading and low math scores. There was a positive linear relationship between pregnancy weight gain and both excess postpartum weight increase and childhood overweight/obesity. Compared with a gestational weight gain z-score 0 SD (equivalent to 20 kg at 37 weeks gestation), a weight gain z-score of +1 SD (27 kg) was associated with 6.3 (0.71, 12) cases of excess weight increase per 1000 women and 4.5 (0.81, 8.2) excess cases of child overweight/obesity per 100 twins. Gestational weight gain was not related to kindergarten academic readiness. CONCLUSIONS: The high prevalence of excess postpartum weight increase and childhood overweight/obesity within the recommended ranges of gestational weight gain for twin pregnancies suggests that these guidelines could be inadvertently contributing to longer-term maternal and child obesity.